Membangun Kepercayaan dalam Lingkungan Belajar Online di Masa Pandemi Covid-19 - Kokoh Sabila, Nanda Putri Khafifah, Riska Alfani, Suci Rahmaida Sihombing (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to analyze the impact of COVID-19 on students' confidence in online-based learning during the pandemic. The subject of this research is for elementary school students. The research method is based on a qualitative descriptive research model. The collected data used in this research is a method that is carried out by interviewing and collecting factual information and data from the relevant sources.